Ocular melanoma and mammary mucinous carcinoma in an African lion - Cagnini, Didier Quevedo [UNESP]; Salgado, Breno S. [UNESP]; Linardi, Juliana L. [UNESP]; Grandi, Fabrizio [UNESP]; Rocha, Rafael M.; Rocha, Noeme Sousa [UNESP]; Teixeira, Carlos Roberto [UNESP]; Del Piero, Fabio; Sequeira, Julio Lopes [UNESP] (Biomed Central Ltd., 2012)
Background: Reports of neoplasms in Panthera species are increasing, but they are still an uncommon cause of disease and death in captive wild felids. The presence of two or more primary tumor in large felids is rarely reported, and there are no documented cases of ocular melanoma and mammary mucinous carcinoma in African lions.Case presentation: An ocular melanoma and a mammary mucinous carcinoma are described in an African lion (Panthera leo). The first tumour was histologically characterized by the presence of epithelioid and fusiform melanocytes, while the latter was composed of mucus-producing cells with an epithelial phenotype that contained periodic acid-Schiff (PAS) and Alcian blue staining mucins. Metastases of both tumor were identified in various organs and indirect immunohistochemistry was used to characterize them. Peribiliary cysts were observed in the liver.Conclusions: This is the first description of these tumor in African lions.
Keywords: Panthera leo; Ocular neoplasms; Mammary gland; Melanocytic neoplasms; Peribiliary cysts